Case report: candidemia in a child with cystic fibrosis with fatal course (Research, Society and Development, 2023)
In the present study we report a case of candidemia in an infant with cystic fibrosis admitted to a Pediatric Intensive Care Unit (PICU) with a fatal course. Six-month-old male patient with a history of productive cough and persistent fever. He was admitted to the PICU of a public hospital in the city of Recife, PE, Brazil, with a diagnosis of dyspnea and cystic fibrosis, with a respiratory infection. Antibiotics were administered, however without success, peripheral blood and transcatheter blood cultures were requested, the isolated agents were Staphylococcus epidermidis and Pseudomonas aeruginosa, respectively. After seven days, the patient presented lesions on the genitalia and persistent fever. Blood and genital lesions were collected, the samples were identified as Candida albicans through the classical taxonomy and the VITEK 120 automated system. The antifungal sensitivity test followed the protocol by the broth microdilution method (CLSI- Clinical and Laboratory Standard Institute, 2008b). The isolates from blood samples were sensitive to amphotericin B with a Minimal Inhibitory Concentration (MIC) of 0.03 µg/mL, 0.12 µg/mL for anidulafungin and 0.25 µg/mL for voriconazole, exhibiting resistance to fluconazole with MIC of 64 µg/mL. C. albicans isolated from the genitalia lesion was sensitive to all the drugs used. The patient was administered nystatin 4 times a day and amphotericin B. The patient improved from the genital lesion and fever. However, after three days, the patient presented cardiac and respiratory deficit that led to cardiac arrest, leading to death.